134k views
3 votes
2x – 3 + 5 if x = 2 please show your work

2 Answers

1 vote

use the substitution method

2(2)-3+5

do the parenthesis first because of PEMDAS

P= parenthesis

E= exponents

M= multiplication

D= division

A= addition

S= subtraction

2(2)-3+5

4-3+5

Then do -3+5

-3+5= 2

4+2

= 6

Answer: 6

User Ticster
by
4.1k points
3 votes

Answer:

6 is your answer.

Explanation:

Note that: x = 2

Plug in 2 for x in the expression given:

2x - 3 + 5 = 2(2) - 3 + 5

Remember to follow PEMDAS as well as the left -> right rule. First, multiply, then subtract, and finally add:

2(2) - 3 + 5 = (2 * 2) - 3 + 5 = 4 - 3 + 5 = 1 + 5 = 6

6 is your answer.

~

User Raklos
by
4.8k points